2005
DOI: 10.1590/s0037-86822005000500005
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa de enterovírus em casos de síndrome de meningite asséptica de Belém, PA

Abstract: RESUMOOs enterovírus pertencem à família Picornaviridae, possuem de 28-30ηm de diâmetro, genoma de RNA de fita simples e polaridade positiva e replicam-se no citoplasma das células hospedeiras (em complexos associados à membrana) 10 . Esses vírus possuem como características favoráveis à transmissão, principalmente feco-oral, a estabilidade em ambientes ácidos (ausência do envelope lipídico) e a resistência aos desinfetantes comuns, além de persistirem viáveis por dias à temperatura ambiente 22 . Como causa de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(4 reference statements)
1
7
0
3
Order By: Relevance
“…Another study in northern Brazil found 13.2% of positive CSF samples for enterovirus using cellular culture, immunofluorescence and neutralization test. The authors reported the importance of determining a national picture of viral meningitis in Brazil since it is still incomplete 18 . Despite the use of different methodologies, the proportion of positive samples was similar to that observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in northern Brazil found 13.2% of positive CSF samples for enterovirus using cellular culture, immunofluorescence and neutralization test. The authors reported the importance of determining a national picture of viral meningitis in Brazil since it is still incomplete 18 . Despite the use of different methodologies, the proportion of positive samples was similar to that observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some viral strains can present low affinity to a specific monoclonal antibody due to mutations leading to antigenic changes in the target epitope occurring, therefore, not recognition by monoclonal antibody (3). Specific MAb directed to EV-4 can present low cross-reaction with EV-30, EV-6 and EV-11 MAbs (3,16). In our study cross-reaction between EV-4 and EV-30 MAbs was observed in 2 samples.…”
Section: Discussionmentioning
confidence: 46%
“…In Spain a study reported cases associated to viral meningitis, during the period from 1988 to 1997 with a high incidence of HEV and the predominance of EV-30 (90%) among non-polio serotype (36). This serotype was responsible for aseptic meningitis epidemics in Japan in 1991 and 1997 (39, 40), Switzerland in 1996 (13), Canada in 1998 (4), Romania in 1999 (5), and more recently published, in Turkey in 1999 (26), France in 2000 (7), Belgium in 2000 (35) and Brazil in 2003 (16,2). Our retrospective study agrees with literature data.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Brazil during the 1960s, Godoy et al [8] reported cases of AM associated with enteroviruses. Later studies have confirmed this association [9][10][11][12][13], including two outbreaks of Echo 30 [14,15]. Classic virology methods, using cell culture, are routinely used to detect EV in clinical specimens.…”
mentioning
confidence: 99%